Purification of influenza virus with Arcton 113. - Brady, M I (1976)
Arcton 113 has proved effective in the removal of host membrane fragments which cosediment with influenza virus during differential centrifugation. The virus appeared morphologically undamaged by the procedure and retained its infectivity, neuraminidase, and hemagglutinating activity. Pyrogenicity, however, was considerably reduced.